Saint-Germain-des-Prés, un mythe de la culture moyenne dans les hebdomadaires des années 1950 - Marie-Astrid Charlier (Contextes)
Through the study of four important weekly newspapers of the 1950s – Paris Match, Radar, L’Express and France-Observateur – this article proposes to explore the representations of existentialism and Saint-Germain-des-Prés, which were totally intertwined, even interchangeable, in the discourse and media imagination of the time. A veritable myth of middlebrow culture, this "extraordinary village" is represented according to two complementary devices: starisation on the one hand, of which Sartre, Prévert and Gréco are the stars, and humour on the other, which mocks the existentialist craze that the newspapers nevertheless invented. Using the American-style news magazine while retaining the devices of the small press of the 19th century and then of the interwar period, the four weeklies created a "Saint-Germain-des-Prés" mythology for middlebrow culture, which was also fed by a large number of novels and films.